Genome Sequence of Anoxybacillus geothermalis Strain GSsed3, a Novel Thermophilic Endospore-Forming Species - Filippidou, Sevasti; Jaussi, Marion; Junier, Thomas; Wunderlin, Tina; Roussel-Delif, Ludovic; Jeanneret, Nicole; Vieth-Hillebrand, Andrea; Vetter, Alexandra; Regenspurg, Simona; Johnson, Shannon; McMurry, Kim; Gleasner, Cheryl D.; et al. (My University, 2015)
Anoxybacillus geothermalis strain GSsed3 is an endospore-forming thermophilic bacterium isolated from filter deposits in a geothermal site. This novel species has a larger genome size (7.2 Mb) than that of any other Anoxybacillus species, and it possesses genes that support its phenotypic metabolic characterization and suggest an intriguing link to metals.